2021
DOI: 10.1136/jclinpath-2021-207527
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of BRAF mutational status with clinical characteristics and survival outcomes of patients with ameloblastoma: the experience of 11 Italian centres

Abstract: AimsAmeloblastoma is a rare odontogenic tumour with an aggressive local behaviour. Mutations in the mitogen-activated protein kinase pathway, namely BRAF V600E mutations, are a common finding. To date, there is no clear correlation between BRAF V600 mutation and clinical outcome.MethodsWe retrospectively reviewed the medical records of patients who underwent surgery for ameloblastoma between May 1998 and June 2018, at 11 participating Italian centres. BRAF mutational status was evaluated by quantitative PCR/py… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…In 2014, the pioneer study by the group of Heikinheimo reported for the first time recurrent activating BRAF p.V600E mutations in ameloblastomas [9]. Considering that MAPK/ERK signaling can be activated by stimulation of transmembrane receptors, including EGFR, and that overexpression of EGFR had previously been reported in ameloblastomas, when [9], [10], [51], [52], [53] e , [54], [55], [56], [57], [58], [59], [60], [61], [62], [63], [64], [65], [ V600E mutation in all five ameloblastic carcinoma samples evaluated and this frequency was much higher than reported by previous studies, and therefore we did not add the results to the other ones when calculating mutation frequency.…”
Section: Ameloblastomamentioning
confidence: 99%
See 3 more Smart Citations
“…In 2014, the pioneer study by the group of Heikinheimo reported for the first time recurrent activating BRAF p.V600E mutations in ameloblastomas [9]. Considering that MAPK/ERK signaling can be activated by stimulation of transmembrane receptors, including EGFR, and that overexpression of EGFR had previously been reported in ameloblastomas, when [9], [10], [51], [52], [53] e , [54], [55], [56], [57], [58], [59], [60], [61], [62], [63], [64], [65], [ V600E mutation in all five ameloblastic carcinoma samples evaluated and this frequency was much higher than reported by previous studies, and therefore we did not add the results to the other ones when calculating mutation frequency.…”
Section: Ameloblastomamentioning
confidence: 99%
“…They further reported the presence of BRAF p.V600E mutation in 67% (23/34) of ameloblastomas by using VE1 immunohistochemistry in cases not suitable for molecular evaluation [52]. Following these pieces of research, several studies have also assessed the presence of BRAF p.V600E in conventional ameloblastoma, either by molecular techniques or a combination of mutation screening and immunohistochemistry, with mutation frequencies varying from 55 to ∼90% [10,[53][54][55][56][57][58][59][60][61][62][63]. In two studies with limited sample numbers, the mutation was detected in all samples [2/2 [64] and 4/4 [65]].…”
Section: Ameloblastomamentioning
confidence: 99%
See 2 more Smart Citations
“…The Changing Clinicopathological Profile of Ameloblastoma: An update Ebtissam Al-erraqi Ameloblastoma (AM) is a locally aggressive benign expansible odontogenic tumor that shows a variety of clinicopathological features. AM reveals a slight preference for affecting males near their third decades with a high rate of local recurrence after resection [1]. Histologically, there are four phenotypes of AM: solid/multicystic, peripheral, desmoplastic and unicystic types.…”
mentioning
confidence: 99%